Impacts of water scarcity on agricultural production and electricity generation in the Middle East and North Africa - Hejazi, Mohamad; Santos Da Silva, Silvia R.; Miralles-Wilhelm, Fernando; Kim, Son; Kyle, Page; Liu, Yaling; Vernon, Chris; Delgado, Alison; Edmonds, Jae; Clarke, Leon (Frontiers in Environmental Science, 2023)
Incorporating the interdependencies between water, energy and food (WEF) within an integrated approach of planning and management could help nations worldwide to address sustainability concerns. This is a topic of great importance for the Middle East and North Africa (MENA) region, where water is a very limited resource. In this study, we develop an analytical framework to analyze the water-energy-food nexus in the MENA region with the goal of informing the formulation of integrated strategies for water, energy and food activities. Our approach is based on an integrated assessment model for the MENA region, which explicitly represents WEF sectors within an economic framework, in tandem with a set of relevant scenarios addressing three key dimensions (socioeconomics, climate and water-management). Using this framework, our study analyzes the current and projected status of water resources in the region, and the potential implications for the agriculture and electricity sectors. Our scenarios demonstrate that water scarcity worsens by the end of the 21st century in most MENA countries, mostly due to growing demands. The impacts of growing scarcity on agriculture are significant, with production projected to drop by 60 percent by 2050 in some countries. On the other hand, and to a lesser extent, water-saving technologies and fuel-switching in the power sector play a key role in mitigating the effects of water scarcity on electricity generation in some parts of the MENA region. Our analysis then underscores the need of reducing the dependence of MENA’s agricultural and energy sectors on water, and of transitioning to renewable energies to reduce water scarcity.